Dengue Hemorrhagic Fever Vector in the Paring Sungai Martapura Indonesia - Arista Triyanti; Rifqoh Rifqoh (Tropical Health and Medical Research, 2019)
Dengue Hemorrhagic Fever (DHF) is one of the public health problems that is still found in Indonesia. This disease always occurs repeatedly due to failure of vector control. Indonesia is the second largest country among 30 countries endemic to DHF. This disease can cause death especially in children. In Sungai Paring Village, January-December 2017, 2 cases of DHF were found. The purpose of this study was to find out the House Index (HI), Countainer Index (CI), Breteau Index (BI), larva free numbers (LFN) , Density Figure (DF) and larvae positive container types. This research is a type of descriptive survey research with total sampling technique. The population in this study were households and containers in the Paring Sungai Martapura Sub-District. The sample in this study was all water reservoirs in 100 respondent's houses. Of the 100 houses surveyed there were 40 positive larvae (HI 40%), 60% ABJ, 41 larvae positive containers from 356 examined containers (CI 11.52%) and positive larvae containers namely, ceramic bath 3 (0.84% ), 1 cement bath (0.28%), 18 used paint buckets (5.06%), 4 large bucket buckets (1.12%), 3 ablutions (0.84%) and 6 plastic drums (1.70%). Based on this research, it is expected that respondents and the community take precautionary measures and control of dengue hemorrhagic fever (DHF) vectors by 3M. For researchers to conduct further research to determine vector density fluctuations